Investigation of gender differences in sleeping comfort at different environmental temperatures - Pan, Li; Lian, Zhiwei; Lan, Li (Indoor and Built Environment, 2012)
Publisher: Sage Publications Sage UK: London, England KerkoCite.ItemAlsoKnownAs: 10.1177/1420326X11425967 2129771:DXF79DIC 5072953:9HQSB6BD openalex: W2150117648
Keywords: _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10316 Sleep and Insomnia; oa:topic:T11373 Effects of Sleep Deprivation and Fatigue on Performance; openalex:n:1; openalex:yes

Cognitive performance was reduced by higher air temperature even when thermal comfort was maintained over the 24–28°C range - Lan, Li; Tang, Jieyu; Wargocki, Pawel; Wyon, David P; Lian, Zhiwei (Indoor Air, 2022)
This study managed to create thermal comfort conditions at three temperatures (24°C-T24, 26°C-T26, and 28°C-T28) by adjusting clothing and air velocity. Thirty- six subjects (18 males and 18 females) were exposed to each of the three conditions for 4.5 h in a design balanced for order of presentation of conditions. During each exposure, they rated the physical environment, their comfort, the intensity of acute subclinical health symptoms, and their mental load, and they performed a number of cognitive tasks. Their physiological reactions were monitored. The subjects rated T24 to be comfortably cool, T26 to be comfortably neutral, and T28 to be comfortably warm. Their self-estimated performance did not differ between conditions but 12 of 14 objective metrics of cognitive performance decreased significantly at the elevated temperatures: compared with T24, their average cognitive performance decreased by 10% at T26 and by 6% at T28. At the elevated temperatures, their parasympathetic nervous system activity (as indicated by PNN50) and their arterial blood oxygen saturation level (SpO2) were both lower, which would be expected to result in reduced cognitive performance. The subjects also rated their acute subclinical health symptoms as more intense and their workload as higher at the elevated temperatures. These results suggest that where cognitive performance is the priority, it is wise to ensure a comfortably cool environment. The present study also supports the use of fans or natural ventilation to reduce the need for mechanical cooling.
KerkoCite.ItemAlsoKnownAs: 10.1111/ina.12916 2129771:IZDK8FG8 4682641:CIQ8XNFD 4682641:M2MHIUAK 5072953:JG79T4UC openalex: W3184331866
Keywords: BE:RELEVANT; C:China; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:cognitive performance; oa:keyword:higher air temperature; oa:keyword:thermal comfort; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11109 Physiological Responses to Heat Stress in Humans; oa:topic:T11244 Impact of Climate Change on Human Health; openalex:n:1; openalex:yes

Sleep and Indoor Air Quality - Lan, Li; Lian, Zhiwei (Handbook of Indoor Air Quality, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:AF3IQJRJ 5072953:UNXXBFHX
Keywords: _important